Immune-metabolic shifts in acute liver failure caused by HEV infection during pregnancy and their association with obstetric outcomes - Anoushka Saxena; Minal﻿; Prabhjyoti Pahwa; Jaswinder Singh Maras; Hamda Siddiqui; Jayesh Kumar Sevak; Yedla Manikya﻿ Mala; Shakun Tyagi; Shiv K. Sarin; Nirupama Trehanpati (Hepatology Communications)
Background:. Hepatitis-E virus (﻿HEV)-induced liver failure during pregnancy leads to maternal and fetal complications. This study investigates the HEV-associated metabolomic and immunological changes to elucidate the worsening of obstetric outcomes in patients with acute liver failure (ALF) due to HEV. Methods:. Pregnant women with (i) acute viral hepatitis, IgM HEV positive (AVH-E, n = 31, Gr.I), (ii) acute liver failure (ALF-E, n = 15, Gr.II), (iii) acute hepatitis but negative for viral infections (non-HEV, n = 30, Gr.III), and healthy (HC, n = 21, Gr.IV) were evaluated at delivery for plasma untargeted metabolomics, cytokine, and immune profiling. Results:. AVH-E and ALF-E (Gr.I, II) showed elevated TNF-α, IL-1β, IL-9, IL-22, and IL-33 compared to HC. In addition, in ALF-E, IFN-γ and IL-12p70 were decreased, but MIP-1α, fractalkine, SDF-1α, IL-22, and IL-33 were increased compared to AVH-E. Both AVH-E and ALF-E had decreased choline, sn-glycero-3-phosphocholine, O-palmitoyl-r-carnitine, and increased taurocholic acid. However, patients with ALF-E had a 2–5-fold decline in these metabolites with raised taurochenodeoxycholic acid. ALF-E showed increased naive T/B cells, decreased CD4, CD8 Tcm, Tem, and plasmablasts, compared to AVH-E contributing to higher failed inductions, preterm births, maternal complications like eclampsia, disseminated intravascular coagulation, preterm premature rupture of membranes, small-for-gestational-age infants, higher rates of intrauterine death, abortion, and mortality. Conclusions:. HEV infection reduces choline, phosphocholine, and palmitoyl carnitine, enhancing inflammation in ALF-E, while increasing taurocholic and taurochenodeoxycholic acids impairs the immune response. These factors together likely contribute to severe obstetric complications, including higher failed inductions, intrauterine death, and maternal and fetal mortality in ALF-E.